2013
DOI: 10.1590/s0001-37652013005000019
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between sandy beach nematodes and environmental characteristics in two Brazilian sandy beaches (Guanabara Bay, Rio de Janeiro)

Abstract: We investigated if the differences in density and nematode communities of intertidal sediments from two Brazilian sheltered sandy beaches were related to environmental characteristics. The upper tide level (UTL) and the low tide level (LTL) of both beaches were surveyed in January (austral summer) and June 2001 (austral winter) during low-spring tides, by collecting samples of nematodes and sediments. Differences in density between beaches, tidal level and seasons, and nematode community structure were investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…In the sandy beach sediment samples as part of this study, Oncholaimus and Viscosia were found to be dominant genera and the reason for their dominance could be attributed to their large size (Fleeger et al 2011) and feeding habit (omnivores/predators) (Wieser 1953). It has been shown in various studies that the family Oncholaimidae which includes genera such as Oncholaimus and Viscosia are usually dominant in sandy environments (e.g., Maria et al 2013;Steif et al 2013). Additionally, we found the family Oncholaimidae to be most species rich as part of this study.…”
Section: Discussionmentioning
confidence: 99%
“…In the sandy beach sediment samples as part of this study, Oncholaimus and Viscosia were found to be dominant genera and the reason for their dominance could be attributed to their large size (Fleeger et al 2011) and feeding habit (omnivores/predators) (Wieser 1953). It has been shown in various studies that the family Oncholaimidae which includes genera such as Oncholaimus and Viscosia are usually dominant in sandy environments (e.g., Maria et al 2013;Steif et al 2013). Additionally, we found the family Oncholaimidae to be most species rich as part of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Fine sediments are generally characterized by the families Desmodoridae and Linhomoeidae, while coarse sediments are dominated by the families Enchelidiidade, Xyalidae, Cyatholaimidae, and Chromadoridae (Wieser 1959;Heip et al 1985;Fonseca and Fehlauer-Ale 2012;Maria et al 2013;Moens et al 2013). Although distinct assemblages along the spectrum occur, we still do not know how these changes occur.…”
Section: Introductionmentioning
confidence: 99%
“…In tropical regions, studies have been performed in Australia (NICHOLAS; HODDA, 1999, NICHOLAS, 2001, HOURSTON et al, 2005, Ecuador (CALLES et al, 2005) and French Polynesia (GOURBAULT et al, 1995). Despite the extensive coastline of Brazil, and the high diversity of the group in sandy beaches (VENEKEY et al, 2010), only a few surveys in the country have studied nematodes at low taxonomic levels (BEZERRA et al, 1997;NETTO et al, 2007;MARIA et al, 2008;MARIA et al, 2013, VENEKEY et al, 2014MELO et al, 2013). Whether studied at phylum, or low taxonomic levels, temporal studies of marine nematodes usually employ a monthly or seasonal scale, and mostly compare periods with or without rain.…”
Section: Introductionmentioning
confidence: 99%